The context of organic residues in archaeological vessels of ceramic and bronze - Merriman, K (2014)
Since the 1970s, the study of molecular organics preserved in archaeological ceramics, commonly referred to as organic residue analysis, has been used to infer vessel use and study dietary, economic, and ritual activities in the past. The purpose of this project is to analyse organic residues from a variety of ancient vessels and attempt to understand further the relationship between molecular organic preservation and vessel characteristics. It has been previously assumed that the absorption of these organics in the ceramic matrix is predominantly responsible for their preservation. The clarification of this or other preservative mechanisms and the further understanding of the relationships of vessels with their contents has a direct impact on the interpretation of organic residues and vessel use. The first section addresses the preservation of molecular organics in pottery vessels from Tel Kabri, Israel; Tel Megiddo, Israel; and Lefkandi, Greece. The one hundred and thirty-three samples from these three sites represent vessels used in domestic, burial, ritual, and elite contexts from the Early Bronze Age through the Iron Age Eastern Mediterranean. The focus of the study is the quantification of residue yields and identification of potential links with vessel properties and characteristics of the ceramic samples. Sequential extractions using two methods, conventional chloroform/methanol solvent extraction and direct FAME extraction/derivatisation, were applied to the sherds to test the absorption and adsorption of organics into ceramic materials. The majority of samples were tested non-destructively, enabling the comparison of residue yields to certain vessel properties and characteristics displayed in the same sherds. Where available, data concerning vessel form, sampling location on the vessel profile, thickness measurements were recorded, and XRF measurements were taken, with this in mind. The second section investigates the question of whether bronze and copper alloy vessels have the capability to preserve molecular organics within their corrosion products. Twenty-two samples of corrosion and associated material from five Early Roman bronze vessels found in cremation burials during the A2 Pepperhill to Cobham project in County Kent, United Kingdom were studied for organic material. These samples provide some of the first evidence that the residues of original content are preserved in copper alloy vessels either through entrapment in or reactions with copper corrosion.